2010
DOI: 10.1186/ar3034
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 upregulation in macrophages participates in the initiation and maintenance of pristane-induced arthritis in rats

Abstract: IntroductionToll-like receptors (TLRs) are involved in both innate and adaptive immune responses and are likely to play a complex role in the pathogenesis of human rheumatoid arthritis (RA) and experimental arthritis. The objective of this study was to identify the key TLR in pristane-induced arthritis (PIA), a rat model for RA, and to clarify its roles in the initiation and maintenance of arthritis.MethodsArthritis in DA rats was induced by pristane and the severity was evaluated by macroscopic and microscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 49 publications
(61 reference statements)
4
60
0
1
Order By: Relevance
“…Synovial fluid nitrite concentration was significantly correlated with serum nitrite concentration in patients with RA (Farrell et al, 1992). Previously, we have found that the plasma NO level is also increased in PIA rat models (Meng et al, 2010). Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Synovial fluid nitrite concentration was significantly correlated with serum nitrite concentration in patients with RA (Farrell et al, 1992). Previously, we have found that the plasma NO level is also increased in PIA rat models (Meng et al, 2010). Fig.…”
Section: Discussionmentioning
confidence: 55%
“…We began to give the medicine one day before induction in the prevention groups, and started to administrate the medicine at 13 d after induction in the treatment groups, as our previous observations showed that the average onset of PIA was at 14 d after induction (Meng et al, 2010). Both groups were given the medicine continuously for 5 d. Two dose groups of BSO for both prevention and treatment were used, with 2.5 and 5 ml/kg BW for low and high doses, respectively.…”
Section: Treatment With Bso and Mtxmentioning
confidence: 99%
“…It is predicted that the autophagy mechanism which is stated by Zhu [13] occurs, so the joint disorder develops without the equal increase of total IL-6. It might be a result of upregulation of TLR 3 on macrophages [16] causes the control of marker cells in rheumatoid diseases [17].…”
Section: Resultsmentioning
confidence: 99%
“…TLR3 was found to be the most significantly up-regulated TLR during pristine induced arthritis in rats, where it appeared in the spleen early after disease initiation. Stimulation of TLR3 with polyI:C also exacerbated disease severity and silencing TLR3 expression reduced disease severity in these animals (Meng et al, 2010). Despite evidence from human studies highlighting the contribution of TLR8 in synovial inflammation, the lack of activation of murine TLR8 by its cognate ligand suggests this PRR is not biologically active in mice (Heil et al, 2004).…”
Section: The Role Of Tlrs In Animal Models Of Ramentioning
confidence: 99%